The Effectiveness of Mental Health Programs for Syrian Refugees in Turkey: A Regional Meta-Review of Interventions - M. Agung Rahmadi; Luthfiah Mawar; Zilva Husayri Zulvan; Nafiza Rizky Ramadhani Lubis; Maulidyah Azzahra; Helsa Nasution; Nurzahara Sihombing; Muhammad Wahyudi Berutu; Annisa Ardianti Br Tarigan (Jurnal Ilmu Kesehatan dan Gizi, 2026)
This meta-review evaluates the effectiveness of diverse mental health programs targeting Syrian refugees in Turkey over the period 2015-2023 through a systematic synthesis of 47 studies involving a total of 12,847 participants. Meta-regression results demonstrate a statistically significant reduction in Post-Traumatic Stress Disorder symptoms, with a large effect size (d = -0.86, 95% CI [-1.02, -0.70], p < .001), as well as a significant reduction in depressive symptoms (d = -0.72, 95% CI [-0.88, -0.56], p < .001) following intervention. Among the therapeutic approaches examined, Cognitive Behavioral Therapy exhibited the strongest therapeutic effect (β = 0.45, p < .001), followed by Eye Movement Desensitization and Reprocessing (β = 0.38, p < .001). Further moderator analysis revealed that group-based interventions were more effective than individual approaches (OR = 1.86, 95% CI [1.42, 2.30]). At the same time, program duration of 12-16 weeks showed a strong correlation with optimal clinical outcomes (r = 0.67, p < .001). These findings extend the results of Acarturk et al. (2022) regarding the effectiveness of CBT and reinforce the argument advanced by Shehadeh et al. (2016) concerning the superiority of group-based approaches, while also indicating a longer optimal intervention duration than previously reported. In contrast to the meta-analysis by Antuña-Camblor & Hernández (2025), which emphasized EMDR, this study identifies CBT as superior to EMDR among Syrian refugees in Turkey. The novelty of this study lies in its comprehensive analysis of program moderator factors and the identification of the most effective intervention duration parameters for the target population.